O prédio escolar no ensino fundamental: diálogo entre arquitetos e sujeitos da educação - Santos, Emerson Souza dos (2020)
As the school has a physical structure that reflects a complex political system, designing a quality school is not just juxtaposing the countless pieces of equipment it makes up, it is worth understanding that the learning space must be thought out and articulated to the demands of its users' needs, providing opportunities establish an identification link. Therefore, in order to welcome the perceptions of the main participants of the educational system about the architectural quality of the school building, this work focuses on investigating the reality of 16 schools in the municipal network of Cascavel, specifically in elementary school I, with the purpose of to rehearse a dialogue about the architectural aspects and the experience of these subjects in designing and occupying these spaces. Within a qualitative investigative proposal, the research unfolds in a methodological script having: bibliographic research, subsidizing and supporting the relationship between space and man and what it translates into messages beyond materiality; documentary research, understanding the relationship of the state with the implementation of educational spaces; field research, scripting approximately 30% of municipal schools as an object of study and welcoming perceptions about the quality of the school space from the principals, teachers, students, in addition to the interview with the infrastructure supervisor of the Department of Education and non-participating observation to school facilities. The analysis of the collected data goes through the method of content analysis where it allows the categorization of these, revealing and subsidizing a wide reflection on the priority needs of the school. At the end of this, it was possible to understand that the views and perceptions of the subjects are heterogeneous, which proves the immobility of innovative actions in face of a closed educational policy and oblivious to the demands of the century's reality. XXI.